IMPLEMENTATION OF GOAT FARMING COACHING AS A MEANS OF IMPROVING THE WORK SKILLS OF INMATES AT THE CLASS IIB CORRECTIONAL INSTITUTION IN TANJUNG BALAI - Turnip, Stevenson Eko Putra; Soge, Markus Marselinus (Universitas Nusa Cendana, 2026)
Correctional institutions are not only responsible for enforcing sentences but also for fostering inmates’ personal development to support their reintegration into society. One form of personality development is spiritual guidance through tahsin and tajwid methods, which aim to improve Qur’anic recitation while shaping more religious and morally grounded individuals. This study examines the implementation of these Islamic spiritual activities at the Class IIA Correctional Facility in Palu and identifies the obstacles encountered in the process. The research uses a qualitative descriptive approach, with data collected through observation, interviews, and document analysis from both primary and secondary sources. The analysis is based on implementation theory and the concept of correctional development (SPPN). The findings indicate that tahsin and tajwid activities contribute positively to inmates’ character development, particularly in fostering discipline, religious awareness, and cooperation with external partners. These activities help create a more structured and value-oriented environment within the correctional institution. However, the implementation of the program still faces several challenges, including limited religious knowledge among inmates, budget and human resource constraints, low intrinsic motivation, and environmental factors that are not fully supportive. Therefore, strengthening institutional support, increasing training resources, and enhancing motivational approaches are necessary to optimize the effectiveness of spiritual development programs for inmates. Keywords: Independence Development; Goat Farming; Work Skills